Promotive and Preventive Health Education: The Effects of Active and Passive Smoking in The Elderly at Yayasan Budi Sosial Batam - Muhammad Putra Hidayat; Devi Lamtiur Gultom; Elisabeth Nona Yunita; Maria Lepang Angelina Koten; Meirlin Sahetapy; Virisya Chumaerotusyifa; Yohanes Iriyanto Neang; Zulfa Linda Harliansyah; Ling Barra (Pengabdian: Jurnal Abdimas, 2023)
Background. Smoking is one of the main risk factors for the health of the elderly. The use of cigarettes in the elderly can cause various health problems. The risks posed by smoking need to be minimized through promotive and preventive efforts. So education is very important because it can increase knowledge for the elderly in achieving a healthy life. Purpose. The purpose of providing health education is to increase the knowledge of the elderly about the dangers and effects of smoking for active and passive smokers. Method. The method of this activity was a lecture. Results. This activity was attended by 10 participants who were willing and by the inclusion criteria made by the activity implementers and carried out on April 17, 2023. Conclusion. This activity is expected to be useful for the elderly and can certainly increase the knowledge of the elderly about the dangers and effects of smoking for active and passive smokers, and of course can improve the health of the elderly in the Batam social welfare foundation.